PENGARUH PERTUMBUHAN PERUSAHAAN, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN DENGAN RISIKO BISNIS SEBAGAI VARIABEL MODERATING - Maya Laura; Amries Rusli Tanjung; Enni Savitri (Jurnal Ekonomi, 2017)
The purpose of this research was to examine the effect of the company's growthprofitability, and firm size affect the dividend policy to moderate business risk.Thepopulation in this research is the property and real estate company in thisresearch across the Property and Real Estate companies listed on the StockExchange was 49 (forty nine) listed companies sampled in this research are asmany as 23 companies that meet the criteria. In analyzing and interpreting thedata, descriptive analysis method and analysis methods verification. Descriptiveanalysis method is used to describe the characteristics of the research variables,whereas the verification method used to test the research hypotheses by usingrelevant statistical tests. While the verification method used in this research isModerate Regression Analysis (MRA).Based on the research hypothesis CompanyGrowth affect the company’s dividend policy at the property and real estate listedon the Indonesia stock exchange. Profitability significant effect on DividendPolicy. Company size doesn’t significant effect on the profitability of the Bank arelisted on the Indonesia Stock Exchange. The business risks can’t strengthen therelationship between the policies dividend. Variabel Company Growth BusinessRisk strengthen the relationship between the profitability of the dividend policy, soH5 accepted. There is the influence of company size on the dividend policy withbusiness risk as a moderating variable. Business Risk and strengthen therelationship between the size of the Company on dividend policy.